Segurança alimentar de produtos derivados de milho consumidos em Cascavel-PR. - Eckert, Raquel Goreti (2011)
Corn (Zea Mays L.) contributes significantly to the human being nourishment because of its nutritional characteristics. However, these characteristics also support fungus growing, which during their secondary metabolism produce toxic substances, named mycotoxins. Among mycotoxins, found more frequently in corn grains and derived products, aflatoxins B1, B2, G1 and G2 can be found and are also rated as cancer developers for human beings, as well as animals. Considering the diversity of sub products from this grain and that most of them is daily on the table of the Brazilian population, this research has the goal of evaluating the safety of corn derivates traded in the city of Cascavel Paraná, focusing on identifying the risk of the population's exposition to aflatoxins. Initially, a population survey was done to check which corn derivates products are the most consumed in the city of Cascavel Paraná, through the application of a questionnaire to the population, stratified into four categories: children (between 2 to 9 years old), teenagers (between 10 to 18 years old), young adults (between 19 to 59 years old) and elderly (above 60 years old). The city was divided into five geographical parts: East, West, North, South and downtown, and in each one of the regions one large supermarket was selected randomly and defined as the place to apply the questionnaires. After carrying out this survey, four samples of each one of the three most consumed corn products were collected. Collection was done every 15 days at the chosen supermarkets. Such samples were submitted to microbiological quality (fungus scoring) physical chemical (moist, ashes, acidity, proteins and lipids levels) and toxicological (identification and quantification of aflatoxins B1, B2, G1 and G2) tests. After finishing these analyses, the likely daily ingestion for AFB1 was estimated with the goal of checking if population was exposed to harms caused by these substances. From the population survey, it was observed that the most consumed corn derivates in the city were corn flour, popcorn and corn starch. Microbiological tests performed in those samples couldn t be analyzed as a pattern indicating quality in the products, considering the absence of a current legislation on this aspect. However, it was observed cultures similar to yeasts in the corn flour harvests whereas fungi similar to genus Aspergillus were noticed in popcorn cultures. Physical chemical tests identified that all samples were suitable to human consumption, considering the evaluated aspects. As for aflatoxins presence, subgroup B1 was detected only in one sample of corn starch, under concentration of 1 μg/kg, or in an amount under the limit recommended to current legislation. In risk analyses, an IDPM of AFBI was estimated to all population categories and the people category identified as eminently in risk were children, with IDPM varying from 0,0963 t 0,1438 ng/kg body weight/day. The conclusion was that even the population layers that acquired products with low aflatoxins incidence and amount, the risk regarding harms of this substance must be periodically checked, considering that in this research only one sample was positive for AFB1. However, IDPM for children was considered going nearly beyond limit.